122k views
5 votes
Consider the quadratic y = –2x² + 4



Consider the quadratic y = –2x² + 4 ​-example-1
User Xiaochen
by
6.2k points

2 Answers

2 votes

Answer:

you need to do in table like I show you

Explanation:

so you need to substitute your y given in the table given and sub in to the equation given which is y = 2x square+4

Consider the quadratic y = –2x² + 4 ​-example-1
User JavierSA
by
5.6k points
4 votes

Explanation:

at -3,y=-2(-3)²+4=-14

at -2,y=-2(-2)²+4=-4

at -1,y=-2(-1)²+4=2

at 0,y=-2(0)²+4=4

at 1,y=-2(1)²+4=2

at 2,y=-2(2)²+4=-4

at 3,y=-2(3)²+4=-14

User Yiinewbie
by
5.8k points